Flexible electrochemical aptasensor for cortisol detection in human sweat. Issue 36 (24th August 2021) - Mugo, Samuel M.; Alberkant, Jonathan; Bernstein, Nina; Zenkina, Olena V.
Abstract : An inexpensive flexible PDMS@CNC/CNT@aptamer sensor for facile detection of cortisol in human sweat with capacity for use as wearable device. Abstract : This communication demonstrates an electrochemical DNA aptasensor for the detection of cortisol in human sweat. The aptasensor was fabricated via layer-by-layer assembly on stretchable polydimethylsiloxane (PDMS) coated with conductive nanoporous carbon nanotube-cellulose nanocrystals (CNC/CNT) film using a linker to a cortisol specific DNA aptamer. The flexible cortisol aptasensor had a dynamic range of 2.5–35 ng mL −1 . The aptasensor precision was determined to be 2.7% relative standard deviation (%RSD) across the concentration dynamic range. The aptasensor was determined to have a limit of detection (LOD) of ∼ 1.8 ng mL −1 . The aptasensor was demonstrated to have high selectivity to cortisol and was unresponsive to interfering species including glucose, sodium lactate, and β-estradiol. The aptasensor was successfully evaluated for the detection of cortisol in human sweat indicative of its high specificity.